Magnetic field induced lattice effects in a quasi-two-dimensional organic conductor close to the Mott metal-insulator transition - De Souza, Mariano [UNESP]; Brühl, Andreas; Strack, Christian; Schweitzer, Dieter; Lang, Michael (American Physical Society (APS), 2012)
We present ultra-high-resolution dilatometric studies in magnetic fields on a quasi-two-dimensional organic conductor κ-(D8-BEDT-TTF) 2Cu[N(CN) 2]Br, which is located close to the Mott metal-insulator (MI) transition. The obtained thermal expansion coefficient, α(T), reveals two remarkable features: (i) the Mott MI transition temperature T MI=(13.6±0.6) K is insensitive to fields up to 10 T, the highest applied field; (ii) for fields along the interlayer b axis, a magnetic field induced (FI) phase transition at T FI=(9.5±0.5) K is observed above a threshold field H c∼1 T, indicative of a spin reorientation with strong magnetoelastic coupling. © 2012 American Physical Society.